2006
DOI: 10.1111/j.1365-2125.2006.02741.x
|View full text |Cite
|
Sign up to set email alerts
|

Predicting sustained virological response and anaemia in chronic hepatitis C patients treated with peginterferon alfa‐2a (40KD) plus ribavirin

Abstract: AimTo assess the likelihood of a sustained virological response (SVR) vs. the likelihood of anaemia in patients with chronic hepatitis C. MethodsData from 1732 patients treated with peginterferon alfa-2a (40KD) plus ribavirin in two randomized, multinational studies were pooled. Probabilities of SVR and anaemia were modelled using the generalized additive logistic model, with numerous clinical variables considered for entry into the model. Baseline haemoglobin was only considered in the analysis for anaemia. R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

8
70
0
1

Year Published

2008
2008
2013
2013

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(79 citation statements)
references
References 18 publications
8
70
0
1
Order By: Relevance
“…The SVR in genotype 1 infected patients was the least in both regimens comparable to other genotypes. These results are similar to other studies carried in France on selected multiethnic patients from France, Egypt and other African countries who were treated with Peg INF alfa 2a based regimen [26,39]. In their study the selected patients were French and Egyptian and other African who had HCV genotype 4 infection on Peg INF alfa 2a they found.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The SVR in genotype 1 infected patients was the least in both regimens comparable to other genotypes. These results are similar to other studies carried in France on selected multiethnic patients from France, Egypt and other African countries who were treated with Peg INF alfa 2a based regimen [26,39]. In their study the selected patients were French and Egyptian and other African who had HCV genotype 4 infection on Peg INF alfa 2a they found.…”
Section: Discussionsupporting
confidence: 90%
“…Other studies have shown no differences in the clinical response of patients infected with HCV genotype 2 and 3, when they were treated with PEG INF alfa2a or INF alfa combination therapies [38,39]. The SVR of Peg INF based regimen was higher than INF based Regimen in all genotypes except for genotype 4 because as 11 patient infected with this genotype had ETR of Peg INF miss the follow up and thus excluded for the data analysis.…”
Section: Discussionmentioning
confidence: 87%
“…Other studies have reported an association between ribavirin exposure after the first dose, or at steady state, as a predictor of SVR rate (32,33). Loustaud-Ratti et al reported that the probability of SVR increased with an increasing in ribavirin AUC 0-12h and AUC 0 -4h after the first dose at a minimum threshold of 3,014 and 1,755 ng*h/mL, respectively.…”
Section: Discussionmentioning
confidence: 97%
“…In addition, patients in these 2 treatment groups had difficulties tolerating their assigned RBV doses, with approximately 75% of patients with severe and one-half of patients with moderate renal impairment requiring RBV dose modification during the first 12 weeks of therapy. Anemia, a common RBV-related adverse event associated with increased RBV exposure (12)(13)(14)21), was the most frequently reported adverse event in patients with moderate and severe renal impairment, reported in 65% and 64% of patients, respectively. Only 20% of patients with moderate and severe renal impairment received their full course of assigned RBV doses for the first 12 weeks.…”
Section: Discussionmentioning
confidence: 99%
“…RBV exposure has been shown to influence both clinical response and toxicity to therapy (9)(10)(11)(12)(13)(14). Current treatment guidelines recommend RBV doses ranging from 200 to 800 mg/day in patients with moderate to severe kidney disease not undergoing hemodialysis and markedly reduced RBV daily doses in patients on dialysis (5).…”
mentioning
confidence: 99%